2022
DOI: 10.48550/arxiv.2201.09309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 mortality prediction: A case study for İstanbul

Abstract: In this paper, we use SEIR equations to make predictions for the number of mortality due to COVID-19 in İstanbul. Using excess mortality method, we find the number of mortality for the previous three waves in 2020 and 2021. We show that the predictions of our model is consistent with number of moralities for each wave. Furthermore, we predict the number of mortality for the second wave of 2021. We also extend our analysis for Germany, Italy and Turkey to compare the basic reproduction number R 0 for Istanbul. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Although R 0 parameter is used frequently, it is model dependent and cannot give information about the mortality rate. Yilmaz et al [16] have used excess mortality rate to understand and predict the peaks of death numbers. They found that R 0 value tend to decrease by time as a result of precautions.…”
Section: Introductionmentioning
confidence: 99%
“…Although R 0 parameter is used frequently, it is model dependent and cannot give information about the mortality rate. Yilmaz et al [16] have used excess mortality rate to understand and predict the peaks of death numbers. They found that R 0 value tend to decrease by time as a result of precautions.…”
Section: Introductionmentioning
confidence: 99%